2022
DOI: 10.1109/jmw.2022.3154886
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Measurements of a Multistatic MIMO Radar Network With Phase Noise Optimized Non-Coherent Signal Synthesis

Abstract: For multistatic radar networks in the upper mm-wave range with a large spacing between its radar sensor nodes, a coherent signal distribution is very complex and thus very costly. Hence, it is desirable to generate the mm-wave signals individually for each radar sensor node, i.e., non-coherently. However, multistatic radar networks using a non-coherent signal distribution for its radar sensor nodes are affected by systematic errors and uncorrelated phase noise, which reduces the resolution and the detection pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…which equals a Doppler frequency offset of δ f D . This offset, however, is extremely small, especially compared to the effect described in (19), and thus can be neglected.…”
Section: Sample Frequency Offsetmentioning
confidence: 95%
See 1 more Smart Citation
“…which equals a Doppler frequency offset of δ f D . This offset, however, is extremely small, especially compared to the effect described in (19), and thus can be neglected.…”
Section: Sample Frequency Offsetmentioning
confidence: 95%
“…Low-frequency coupling using cables [14], [15] and the use of a separate synchronization signal [16], [17] are among the most typical variants. Alternatively, the necessity of synchronization can be avoided by using costly high-quality signal sources with a very low phase noise [18], [19]. However, all these approaches lack the flexibility and simplicity of plain uncoupled radar sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, a distribution network for the reference clock is necessary, and additional phase noise generated by each radar's phase-locked loop (PLL) and voltage-controlled oscillator (VCO) cannot be eliminated. The work in [16] shows that coherent DoA estimation is possible in an uncoupled radar network, but it still suffers from a phasenoise-induced performance loss.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the relationship between array and position of the network nodes, the resulting VNA, and the networkbased DoA estimation, it is shown that for a proper DoA estimation a radar network allowing for a flexible VNA design is crucial. This is not possible with the networks presented in [15], [16], and in [19], [20], as the bistatic subarrays will always be in the middle of the two monostatic subarrays.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple-Input-Multiple-Output (MIMO) radar networks, consisting of multiple individual MIMO sensors, offer the possibility to place the sensors further apart and thereby increase the aperture of the virtual antenna array. Multiple of MIMO radar networks have already been realized and analyzed [3], [4], [5], [6], [7], [8]. The different implementations are divided into three network topologies: Radio Frequency (RF) coupled networks, Low Frequency (LF) coupled networks and uncoupled networks.…”
Section: Introductionmentioning
confidence: 99%